2019
DOI: 10.1126/scitranslmed.aav7561
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ enhances cell-mediated cytotoxicity against keratinocytes via JAK2/STAT1 in lichen planus

Abstract: Lichen planus (LP) is a chronic debilitating inflammatory disease of unknown etiology affecting the skin, nails, and mucosa with no current FDA-approved treatments. It is histologically characterized by dense infiltration of T cells and epidermal keratinocyte apoptosis. Using global transcriptomic profiling of patient skin samples, we demonstrate that LP is characterized by a type II interferon (IFN) inflammatory response. The type II IFN, IFN-γ, is demonstrated to prime keratinocytes and increase their suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 53 publications
6
108
1
5
Order By: Relevance
“…Specifically, it is predominantly produced by natural killer cells, group 1 innate lymphoid cells, yδ T cells and CD8+ cytotoxic T cells as well as CD4+ Th1 cells [as reviewed in ( 124 )]. Its receptor (IFNyR) signals via the JAK1/JAK2 and STAT1/STAT2 pathway ( 107 , 125 ). Shao et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it is predominantly produced by natural killer cells, group 1 innate lymphoid cells, yδ T cells and CD8+ cytotoxic T cells as well as CD4+ Th1 cells [as reviewed in ( 124 )]. Its receptor (IFNyR) signals via the JAK1/JAK2 and STAT1/STAT2 pathway ( 107 , 125 ). Shao et al.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation with eNA results in a pronounced expression of typical ID-associated cytokines within different keratinocyte models. IFNy, mainly produced by lymphocytes, is known to play a pivotal role in the pathogenesis of diseases featuring ID ( 107 109 ), and has been shown to induce typical morphological changes in human epidermis equivalents, in vitro ( 110 ). Herein, we aim to deliver an in-depth analysis of differentially regulated genes in our ID model and furthermore present synergistic effects of endogenous nucleic acids in addition to IFNy on human keratinocytes.…”
Section: An In Vitro Model To Study Interface Dermmentioning
confidence: 99%
“…Treatment of LP is mainly based on oral or topical glucocorticosteroids, phototherapy, retinoids or immunosuppressive drugs such as cyclosporine or methotrexate (107). There is growing evidence that LP is a Th1 driven disease (10, 108, 109), although Th17-associated cytokines have also been reported in LP (110112). A recent study showed that the T cell infiltrate presents high numbers of Th1/Tbet + cells and the presence of IL-17A + cells, disposed beneath the basal cells of the epidermis (10).…”
Section: Lichen Planusmentioning
confidence: 99%
“…LP is the third most common inflammatory skin disease, characterized by epidermal keratinocyte death and dense infiltration of T cells in the dermis 173 . We previously provided evidence of the role of IFN-γ in the cell-mediated cytotoxicity of keratinocytes in LP 174 . Recently, several studies explored the function of EVs in LP.…”
Section: Ev Involvement In the Pathophysiology Of Inflammatory Skin Dmentioning
confidence: 99%